(untitled) (Revista Electrónica REDINE, 2018)
This study is formed within the special project mode, supported by an investigation of descriptive field, in order to determine the need to design learning objects for people with visual disabilities. This research is focused on cognitive and constructivist theories. The study subjects were composed of five (5) students with subjects with visual disabilities in the UPEL-IPB developed in tree plases; the first is the need for design diagnosis. The second phase focused on the elaboration of the learning object. Finally the third corresponded to the validation by experts in statistics and technology phase, also by potential users. This results shown that the learning objects meet innovation, indicators, accessibility, versatily, autinomy and impendence to be incorporated into the pedagogical activities and also be at the disposal of students with visual impairment.